Psychological Issues Encountered By Students In Learning English Within The Pesantren Environment - Nashihin, Muhammad; Shofi Zuhri, Moh; Kavin Lidinillah, Moh (JELP Journal of English Language and Pedagogy, 2024)
The prominence of the English language in various global domains has positioned it as the most dominant international language. However, learning English, especially within Islamic boarding schools ("pesantren"), presents unique challenges. This study focuses on the psychological issues faced by students when learning English within the pesantren context. Three significant psychological problems were identified through observations and interviews with 30 students: lack of learning motivation, lack of self-confidence, and excessive anxiety. Firstly, the lack of learning motivation stems from factors like academic boredom, inadequate understanding of material relevance, and perceived irrelevance of English. This study emphasizes the negative correlation between learning motivation and academic performance, highlighting the need for engaging teaching methods. Secondly, the lack of self-confidence affects students' academic performance. Social comparisons and feelings of inadequacy due to past experiences hinder students' self-assurance. Psychological support programs are necessary to bolster self-confidence and overcome these challenges. Thirdly, excessive anxiety in the academic environment adversely impacts students' performance. The correlation between anxiety levels and academic performance underscores the importance of holistic approaches to manage anxiety. Creating a relaxed environment, offering counseling support, and teaching stress management skills can assist students in coping effectively. The study highlights the crucial role of addressing psychological challenges to enhance students' academic performance. Teachers, institutions, and counselors should collaborate to address learning motivation, self-confidence, and anxiety, optimizing students' potential within a supportive educational context